Memory, migration and guilt. Issue 1 (1st April 2013) - Assmann, Aleida; Schwarz, Anja
For a while now, German and Australian societies have been in the process of negotiating the understanding of their nations' guilty pasts, constituted by the atrocities committed by Germans during the Third Reich on the one hand and the history of Indigenous dispossession in Australia on the other. These concerns mark a reorientation of national memory politics towards an empathic recognition of the nation's victims. This article discusses the ways in which immigrants are implicated in these current renegotiations of 'negative national memories' in both countries